Oldies but Goldies mtDNA Population Variants and Neurodegenerative Diseases - Chinnery, Patrick F.; Gomez-Duran, Aurora (Frontiers in Neuroscience, 2018)
mtDNA is transmitted through the maternal line and its sequence variability, which is population specific, is assumed to be phenotypically neutral,. However, several studies have shown associations between the variants defining some genetic backgrounds and the susceptibility to several pathogenic phenotypes, including neurodegenerative diseases. Many of these studies have found that some of these variants impact many of these phenotypes, including the ones defining the Caucasian haplogroups H, J and Uk, while others, such as the ones defining the T haplogroup, have phenotype specific associations. In this review, we will focus on those that have shown a pleiotropic effect in population studies in neurological diseases. We will also explore their bioenergetic and genomic characteristics in order to provide an insight into the role of these variants in disease.